2022
DOI: 10.1088/1742-6596/2244/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff limitation of left-hand polarization wave and candidates for further enhanced producing multicharged ions on ECRIS

Abstract: Based on experimentally obtained plasma parameters in an electron cyclotron resonance (ECR) ion source (ECRIS) and theoretical considerations, it is turned out the essential factor that is currently presumed to define the increase in multicharged ion current in ECRIS is not simply the density limit of ordinary wave and right-hand cutoffs, but is also higher density one of left-hand cutoff. There are two response guidelines that can be considered to make it possible to overcome limitations, except for the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…at the same frequency is about 2.5-3.5×10 17 m -3 in good agreement with the measurement results. [6]…”
Section: Theoretical Background 21 Dispersion Relations Resonances An...mentioning
confidence: 99%
See 1 more Smart Citation
“…at the same frequency is about 2.5-3.5×10 17 m -3 in good agreement with the measurement results. [6]…”
Section: Theoretical Background 21 Dispersion Relations Resonances An...mentioning
confidence: 99%
“…The conventional solution to this problem is to increase the resonance frequency of microwaves with frequency tuning technique and increase the magnetic field strength as a means of increasing the cutoff density of electromagnetic (EM) wave propagation. [6] Therefore, from the viewpoint of heating by EM waves, there are two ways to break through the limit of multiply charged ion current. In the highfrequency EM waves, one method is to induce resonance by mode conversion from EM waves with various cutoff densities, etc., to electrostatic waves with no cutoff densities.…”
Section: Introductionmentioning
confidence: 99%
“…Accessibility conditions for EM wave propagation were investigated using the ne value obtained by probe measurements and their previously obtained z-direction distribution measurement results. [4] Regarding the conditions corresponding to CSD already shown in figure 3, figure 5 shows the ECR resonance point(black), O-cutoff(green), L-cutoff(blue), and LHR resonance point(brown). Each figure shows LHR regions for Ar +~4+ ions.…”
Section: Lhr Accessibility Conditionsmentioning
confidence: 99%
“…Current ECRIS has a density limit due to the left-hand cutoff density limitation, and it was suggested that this might cause a multicharged ion current limit basically. [4] Conventionally conducted solution for these problems is to increase microwave frequency and the magnetic field strength as a means of increasing the cutoff density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation